Assistance in Learning to Count for SDN Ngimbang Students through Singing - Siti Alfiatur Rohamaniah; Novita Eka Chandra; Awawin Mustana Rohmah; Sinta Nurjanah Ely; Ani Habibatun Nisa; Alda Dwi Valentino (Shof Literacy Community, 2024)
This activity aims to assist students learning to count who are still experiencing difficulties at Ngimbang State Elementary School. Mastery of mathematical calculations at a basic level is very important as an effort to build a strong foundation in understanding basic mathematics. This community service uses the singing method. The results of this service were attended by 30 grade 1 students, with 20 students able to count well and 10 students who were still lacking. This mentoring activity was carried out well. Students were very enthusiastic about following it. This service is a community service that aims to improve the numeracy skills of grade 1 students through the use of singing as a fun and interactive learning approach. It can be seen that grade 1 students who previously had absolutely no understanding of counting, have now made significant progress. The use of singing media is a very effective and exciting learning method for improving numeracy skills for elementary school students.